"I would love if there was a young woman to encourage us, to ease our anxiety which we would have if we were alone": Adapting the Mothers2Mothers Mentor Mother Model for adolescent mothers living with HIV in Malawi. - Nicole B Carbone (PLoS ONE, 2019)
Background Pregnant and post-partum adolescent girls and young women (AGYW) living with HIV in sub-Saharan Africa experience inferior outcomes along the prevention of mother-to-child transmission of HIV (PMTCT) cascade compared to their adult counterparts. Yet, despite this inequality in outcomes, scarce data from the region describe AGYW perspectives to inform adolescent-sensitive PMTCT programming. In this paper, we report findings from formative implementation research examining barriers to, and facilitators of, PMTCT care for HIV-infected AGYW in Malawi, and explore strategies for adapting the mothers2mothers (m2m) Mentor Mother Model to better meet AGYW service delivery-related needs and preferences. Methods Qualitative researchers conducted 16 focus group discussions (FGDs) in 4 Malawi districts with HIV-infected adolescent mothers ages 15-19 years categorized into two groups: 1) those who had experience with m2m programming (8 FGDs, n = 38); and 2) those who did not (8 FGDs, n = 34). FGD data were analyzed using thematic analysis to assess major and minor themes and to compare findings between groups. Results Median participant age was 17 years (interquartile range: 2 years). Poverty, stigma, food insecurity, lack of transport, and absence of psychosocial support were crosscutting barriers to PMTCT engagement. While most participants highlighted resilience and self-efficacy as motivating factors to remain in care to protect their own health and that of their children, they also indicated a desire for tailored, age-appropriate services. FGD participants indicated preference for support services delivered by adolescent HIV-infected mentor mothers who have successfully navigated the PMTCT cascade themselves. Conclusions HIV-infected adolescent mothers expressed a preference for peer-led, non-judgmental PMTCT support services that bridge communities and facilities to pragmatically address barriers of stigma, poverty, health system complexity, and food insecurity. Future research should evaluate implementation and health outcomes for adolescent mentor mother services featuring these and other client-centered attributes, such as provision of livelihood assistance and peer-led psychosocial support.